دور التحكيم في حل منازعات الملكية الفكرية - صوالح بدادي ،شفاء; غريسي ،نور الايمان; وبـري ،مـنـار (جامعة الوادي University of El Oued, 2024)
نظرا للتطورات التكنولوجية التي يشهدها العالم وظهور ما يعرف باقتصاد المعرفة وتزايد اهتمام الباحثين ببراءات الاختراع والابتكارات والأفكار، ونظرا للاعتداءات والانتهاكات الصارخة لهاته الأفكار والاختراعات كان لابد من إيجاد وسائل حماية تضمن الحقوق لأصحابها، وهو ما سعت إليه الدول من خلال تنظيم اتفاقيات وإنشاء منظمات دولية تعنى بحماية هذه الحقوق، وكان من أبرز ما تم إنشاؤه المنظمة العالمية للملكية الفكرية التي تعمل على حماية وتنظيم مجال الملكية الفكرية وفض النزاعات الناشئة حولها، بالإضافة إلى إنشاء منظمة التجارة العالمية التي هدفت لتحرير التجارة الدولية، وقد كان للمنظمتين تعاون وتنسيق بينهما في إطار حماية الملكية الفكرية وتسوية منازعاتها وذلك من خلال طرق سلمية وشبه قضائية كان التحكيم أبرزها. Due to technological developments in the world, the emergence of the so-called knowledge economy and the increasing interest of researchers in patents, innovations and ideas Given the blatant violations and abuses of these ideas and inventions, it was necessary to find protections that guarantee the rights of their owners. This is what States have sought through the organization of conventions and the establishment of international organizations concerned with the protection of these rights. The World Intellectual Property Organization (WIPO), which works to protect and regulate the field of intellectual property and resolve disputes arising around it, The World Trade Organization aims to liberalize international trade. The two organizations have had cooperation and coordination within the framework of intellectual property protection and settlement of their disputes through peaceful and quasi-judicial methods, most notably arbitration.
ماستر اعمال